Evaluasi Teknik Steganografi dan Efektivitasnya dalam Perlindungan Informasi - Rizal Fahmi; Baihaki Rizky; M. Zakki Mubaraq; Rahmi Sahara; Indah Sari Panjaitan (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
Information security is a critical issue in the digital era, particularly in the exchange of confidential data over public networks. Steganography offers a solution by hiding information within digital media so that its existence is not detected. This study aims to evaluate the effectiveness of two popular steganography techniques: Least Significant Bit (LSB) and Discrete Cosine Transform (DCT) in terms of imperceptibility and robustness. The method used involves embedding text messages into image media and measuring quality using Mean Squared Error (MSE) and Peak Signal- to-Noise Ratio (PSNR). The results show that the LSB technique offers better imperceptibility with a higher average PSNR value (55 dB) compared to DCT (42 dB). However, DCT demonstrates superior robustness against compression attacks and noise addition. This research concludes that the selection of steganography techniques must be adjusted to specific needs, balancing hiding capacity and resistance to manipulation.